Inter-professional collaboration of nurses and midwives with physicians and associated factors in Jimma University specialized teaching hospital, Jimma, south West Ethiopia, 2019: cross sectional study - Eneyew Melkamu; Solomon Woldemariam; Abera Haftu (BMC, 2020)
Abstract Background Inter-professional collaboration between professionals is crucial in health care where most of the activities are undertaken in a team. One of these collaborations is the collaboration of nurses and midwives with physicians. The main objective of this study was to assess interprofessional collaboration of nurses and midwives with physicians and associated factors at Jimma University specialized teaching hospital from March 20 to April 8, 2019. Methods An institution-based cross-sectional study was conducted among 358 nurses and 52 midwives who are working in Jimma University Specialized teaching hospital using a structured self-administered questionnaire. Study units were selected by simple random sampling using the lottery method. The result was summarized using descriptive statistics and statements. The level of significance was set at a p < 0.05. Result The overall response rate was 99.76%. Around two-third, 66.7% (n = 273) of participants had a satisfactory inter-professional collaboration with physicians and 238 (58.2%) had good relationship with physicians. Again 234 (57.2%) of participants had a favorable attitude towards interprofessional collaboration with physicians. Moreover, statistical significance was obtained on the relationship of participants with physicians (p = 0.000), the experience of disruptive behavior (p = 0.000), attitude towards interprofessional collaboration with physicians (p = 0.000) and occupational status (p = 0.001). Conclusion The majority of the participants had a satisfactory inter-professional collaboration with physicians and four of the many possible factors under consideration were finally found statistically significant. Again, it was revealed that nurses and midwives did not significantly differ in their inter-professional collaboration with physicians.